2008
DOI: 10.1111/j.1399-3046.2008.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and health‐related quality of life in adolescent liver transplant recipients

Abstract: Adolescence is a particularly high-risk period for non-adherence with post-transplant medical regimens. There remains a lack of research investigating factors related to non-adherence in adolescent LT recipients. The present study empirically assessed the relationship between adherence and HRQOL in adolescent LT recipients. Participants included 25 adolescents (mean = 15.1 yr, range 12-17.9) and their parent/guardian(s). Adherence was assessed using multiple indices including clinician-conducted interviews, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
145
4
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(159 citation statements)
references
References 38 publications
(55 reference statements)
7
145
4
2
Order By: Relevance
“…(8). This has been confirmed in later studies (9)(10)(11). However, these studies fail to take neurodevelopment into consideration and assume the psychological perception of a child is the same as that of an adolescent.…”
Section: Liver Transplantation (Lt) Has Become the Standard Treatmentmentioning
confidence: 80%
See 2 more Smart Citations
“…(8). This has been confirmed in later studies (9)(10)(11). However, these studies fail to take neurodevelopment into consideration and assume the psychological perception of a child is the same as that of an adolescent.…”
Section: Liver Transplantation (Lt) Has Become the Standard Treatmentmentioning
confidence: 80%
“…Furthermore, a majority of studies rely on parent report rather than self-report, which has shown to be an unreliable method of assessing HRQL (12,13). The limitations of published studies notwithstanding, attempts to identify factors associated with reduced quality of life (QoL) have been described previously (9,(14)(15)(16) (17) and was based on a structured definition of HRQL specific to young people (18 (20) and has been used in previous studies of HRQL in children after LT (9)(10)(11)(14)(15)(16)21 …”
Section: Liver Transplantation (Lt) Has Become the Standard Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4][5][6][7][8][9][10][11] Reasons for nonadherence are varied and include, but are not limited to, high costs of IST, adverse drug effects, confusion regarding dosing schedule, psychiatric disorders, beliefs that IST is not effective, health care and work related problems, traveling away from home, and changes in recommended doses of therapy. 4,[11][12][13][14][15] Although various methods have been used to assess nonadherence, no one measure is currently considered the gold standard. 16 To implement strategic interventions targeting IST nonadherence in practice-based settings, measures of nonadherence are needed that are valid and reliable as well as inexpensive, practical, and easily administered.…”
Section: Immunosuppressant Therapy Adherence Scale Formentioning
confidence: 99%
“…It is considered to be a downside of maturation as the process of developing autonomy, separating from parents and assimilating with peers progresses. 151 Education and convenience of the immunosuppressive regimen are core to the cause of promoting drug adherence. The latter is aided by the least possible number of medications and time points during the day when these need to be taken.…”
Section: Adherence or Lack Of It After Liver Transplantationmentioning
confidence: 99%